2023
DOI: 10.3389/fphys.2023.1244190
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA-mediated ceRNA network of Altica viridicyanea is involved in the regulation of the Toll/Imd signaling pathway under antibiotic treatment

Yipeng Ren,
Juhong Chen,
Yuan Wang
et al.

Abstract: Long noncoding RNAs (lncRNAs) play significant roles in the regulation of mRNA expression or in shaping the competing endogenous RNA (ceRNA) network by targeting miRNA. The insect gut is one of the most important tissues due to direct contact with external pathogens and functions in the immune defense against pathogen infection through the innate immune system and symbionts, but there are limited observations on the role of the lncRNA-involved ceRNA network of the Toll/Imd pathway and correlation analysis betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…At first, combined with our previous study, we found a classical Toll/ Imd-MAPK/NF-κB axis that contains upregulated and downregulated DEMs and target genes in response to changes in the gut bacteria of A. viridicyanea (Ren et al, 2023). We further observed that gut bacterial shifts also affected the expression changes of metabolism-related miRNAs, implying that gut bacteria are most likely linked to miRNA profiles, which could play significant roles in adaptive evolution and maintaining homeostasis of A. viridicyanea.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…At first, combined with our previous study, we found a classical Toll/ Imd-MAPK/NF-κB axis that contains upregulated and downregulated DEMs and target genes in response to changes in the gut bacteria of A. viridicyanea (Ren et al, 2023). We further observed that gut bacterial shifts also affected the expression changes of metabolism-related miRNAs, implying that gut bacteria are most likely linked to miRNA profiles, which could play significant roles in adaptive evolution and maintaining homeostasis of A. viridicyanea.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, the association of gut bacterial changes from 16S rRNA amplicon sequencing and DEMs from sRNA‐seq indicated that different gut bacteria at the genus level significantly positively or negatively associated with miRNA profiles in immune‐ and metabolism‐related pathways. At first, combined with our previous study, we found a classical Toll/Imd‐MAPK/NF‐κB axis that contains upregulated and downregulated DEMs and target genes in response to changes in the gut bacteria of A. viridicyanea (Ren et al., 2023 ). We further observed that gut bacterial shifts also affected the expression changes of metabolism‐related miRNAs, implying that gut bacteria are most likely linked to miRNA profiles, which could play significant roles in adaptive evolution and maintaining homeostasis of A. viridicyanea .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Accumulating evidence have shown that various types of ncRNAs, such as circRNAs and lncRNAs, are able to regulate diverse activities of insects like development and immunity through ceRNA networks using miRNAs as a bridge ( Gao et al, 2023 ; Ren et al, 2023 ). CircRNAs, mRNAs, and any other RNAs that share common miRNA response elements (MREs) can competitively bind with miRNAs, acting as an RNA sponge to block and inhibit miRNAs from binding to their target sites ( Tay et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%